Traces of Kiosk Masjid Tradition in Edirne Rustem Pasha Caravanserai - Nesrin Çiçek Akçıl Harmankaya (Sanat Tarihi Yıllığı)
The Rüstem Pasha Caravanserai in Edirne and its kiosk masjid have an important place among the Ottoman period staging-post structures, with the kiosk masjid constituting the subject of this study. Rüstem Pasha Caravanserai is located in Edirne’s city center and was built by Mimar Sinan in 1560-61 by order of the Grand Vizier Rüstem Pasha. The building consists of two parts, with a large courtyard and a small courtyard, and is considered the most advanced example of a twostory caravanserais. The middle of the large courtyard in the caravanserai, was known to have had a kiosk masjid on top of the shadirvan. This kiosk masjid no longer exists, having been destroyed during the Ottoman-Russian War of 1877-1878. The building, has yet to be adequately studied, and a drawing of the building in the Süheyl Ünver archive and dating from 1830 states the buildingto have belonged to Tosyavizade Rifat Osman and to have had particular importance in its time. The kiosk masjid, whose name encountered in the Rüstem Pasha foundation charter, was also very important an example that had been applied among the caravanserais of the Ottoman period. This study examines the historical and architectural features of the kiosk masjid and its drawing and compares it to examples of similar kiosk masjids in Anatolia. The study also evaluates the place and importance of the kiosk masjid in Mimar Sinan’s architecture. Based on the Rüstem Pasha foundation charter and archive documents, the study starts off by determining that a kiosk masjid had been built in the Rüstem Pasha Caravanserai. After the Anatolian Seljuk caravanserais and the inns of the Early Ottoman period, the tradition of the kiosk masjid was understood to have been continued by Mimar Sinan in the caravanserai architecture of the Ottoman period.